Peacebuilding women in international perspective - Porter, Elisabeth J. (Routledge advances in international relations and global politics)
'Peacebuilding' elucidates some key ideas and practices underlying women's peacebuilding, highlighting positive examples of their contribution to peacebuilding in conflict zones and in societies pursuing transitional justice.